Serum leptin and cholesterol values in suicide attempters - Atmaca, M; Kuloglu, M; Tezcan, E; Ustundag, B; Gecici, O; Firidin, B (Karger, 2002)
The growing number of studies examining the relationship between suicide and lipid metabolism are based upon studies suggesting that cholesterol-lowering procedures may incease the risk of death due to suicide or impulsive-aggressive behavior. Leptin seems to be strongly associated with lipid metabolism. In the present study, serum total cholesterol and leptin levels were compared in 24 suicide attempters and 24 healthy controls. The patients with suicide attempts had significantly lower serum cholesterol and leptin levels than controls. There was a positive correlation between cholesterol and leptin levels in both groups. Our results suggest that suicide attempts seem to be associated with decreased serum cholesterol and leptin levels. Copyright (C) 2002 S. Karger AG, Basel.
Keywords: leptin; cholesterol; suicide